Detection of Toll-like receptor 2 (TLR2) mutation in the lepromatous leprosy patients - Kang, Tae-Jin; Chae, Gue-Tae (FEMS immunology and medical microbiology, 2001)
Toll-like receptor 2 (TLR2) is critical in the immune response to mycobacterial infections and the mutations in the TLR2 have been shown to confer the susceptibility to severe infection with mycobacteria. To define this, we screened the intracellular domain of TLR2 in 131 subjects. Groups of 45 lepromatous and 41 tuberculoid leprosy (TT) patients and 45 controls were investigated. Ten subjects among the lepromatous leprosy (LL) patients had a band variant detected by single-stranded conformational polymorphism. DNA sequencing detected a C to T substitution at nucleotide 2029 from the start codon of the TLR2. The mutation would substitute Arg to Trp at amino acid residue 677, one of the conserved regions of TLR2. In our results, the mutation was involved in only LL, not TT and control. Thus, we suggest that the mutation in the intracellular domain of TLR2 has a role in susceptibility to LL.